2022
DOI: 10.1111/jvim.16466
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia in dogs with chronic hypoxic pulmonary disease

Abstract: Background: Prolonged tissue hypoxia caused by chronic pulmonary disease is commonly regarded as an important mechanism in the development of secondary polycythemia, but little clinical data are available to support this hypothesis.Objective: To study the prevalence and severity of erythrocytosis accompanying chronic hypoxic pulmonary disease in dogs.Animals: Forty-seven dogs with hypoxic chronic pulmonary disease, 27 dogs with nonhypoxic chronic pulmonary disease, and 60 healthy controls.Methods: Dogs with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…In dogs, prolonged tissue hypoxia caused by chronic lung disease is generally considered an important mechanism for the development of secondary polycythemia [ 29 ]. Although several studies have investigated the prevalence of polycythemia in dogs with chronic hypoxemia, its occurrence is rare [ 30 , 31 ]. In this study, no apparent increase in erythrocytes was observed in the lung disease group, suggesting that a pathology different from that in humans was involved.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, prolonged tissue hypoxia caused by chronic lung disease is generally considered an important mechanism for the development of secondary polycythemia [ 29 ]. Although several studies have investigated the prevalence of polycythemia in dogs with chronic hypoxemia, its occurrence is rare [ 30 , 31 ]. In this study, no apparent increase in erythrocytes was observed in the lung disease group, suggesting that a pathology different from that in humans was involved.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the ethanol extract of D. ochreata leaves did not affect polycythaemia in the test animals. 23 All treatment groups showed normal leukocyte values, except for the female group, 800 mg/kg BW, with leukocyte values above the normal range (Table 3). Analysis of leukocyte levels in female rats at a dose of 800 mg/ kg BW significantly differed ( p<0.05) from the control group.…”
Section: Haematology Evaluationmentioning
confidence: 91%